2013
DOI: 10.2474/trol.8.7
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Textured Surface in 2D Parallel Bearings Governed by the Reynolds Equation Including Cavitation and Temperature

Abstract: One-dimensional textured parallel bearings have been successfully optimized for the maximum load capacity or the minimum friction coefficient using a unified computational approach. However, there is no efficient approach allowing for the optimization of two-dimensional (2D) bearings. The work conducted is, in most cases, by "trial and error", i.e. changes are introduced and their effects studied, either experimentally or through numerical parametric studies. This is time consuming and costly. In this paper, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 54 publications
1
14
0
Order By: Relevance
“…They show that in presence of surface texturing, the average temperature of the lubricating film reduces. In work of Guzek et al [32], upon an optimization of the surface texturing parameters in parallel bearings, they numerically solved the Reynolds equation, considering mass-conserving cavitation and viscosity changes due to temperature change. They showed that the decrease in viscosity due to the temperature rise can reduce the load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…They show that in presence of surface texturing, the average temperature of the lubricating film reduces. In work of Guzek et al [32], upon an optimization of the surface texturing parameters in parallel bearings, they numerically solved the Reynolds equation, considering mass-conserving cavitation and viscosity changes due to temperature change. They showed that the decrease in viscosity due to the temperature rise can reduce the load carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the present focus is on the design of the interface and not on the analysis of a prescribed texture (see the work of Gropper et al for a review of commonly prescribed texture geometries and related analysis approaches). One advantage of existing design studies is their ability to address the problem directly through a complete mesoscale analysis in the lack of a clear scale separation that is necessary for the application of the homogenization theory . Another advantage is that, considering the large number of design variables that are typically needed in topology optimization, they can restrict the design space to achieve optimal designs in a numerically more efficient manner .…”
Section: Introductionmentioning
confidence: 99%
“…One advantage of existing design studies is their ability to address the problem directly through a complete mesoscale analysis in the lack of a clear scale separation that is necessary for the application of the homogenization theory. [17][18][19][20] Another advantage is that, considering the large number of design variables that are typically needed in topology optimization, they can restrict the design space to achieve optimal designs in a numerically more efficient manner. [21][22][23] On the other hand, an ability to endow interfaces with very finely distributed intricate geometries using modern manufacturing methods provides an opportunity to question and explore the possibilities of unrestricted microscopic interface geometry design via homogenization-based topology optimization.…”
Section: Introductionmentioning
confidence: 99%
“…To texture the inlet, the first texture row is simply elongated towards the inlet. Only partially textured pads and angular sector shaped textures with flat bottom profile are considered, as this type of texture pattern most closely reassembles a stepped configuration, which has been shown to have the most beneficial impact on the bearing performance [7,8].…”
Section: Bearing Geometry and Film Thicknessmentioning
confidence: 99%